Peningkatan Penguasaan Konsep Matematika Melalui Pendekatan Saintifik - Ahmad Sofi Yullah; Nur Azizah; Ariyaningsih Ariyaningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of the research is to provide training and enhance students' understanding of mathematical concepts. The methods used in this activity are direct practical methods and lecture methods. The service was conducted at SDN 2 Kembiritan Jl. Raya Pandan. RT / RW: 1 / 7, Dusun Temurejo, Kembiritan, Kec. Genteng, Kabupaten Banyuwangi, East Java 68465. The implementation of community service activities at SDN 2 Kembiritan was carried out in several stages, namely preparation, execution, and closure. The results of the community service showed that strengthening mathematical concepts with a scientific approach can enhance students' understanding of mathematical concepts. This was proven by the test results, which showed an improvement after the scientific approach was applied.